A Conserved Tyrosine Residue in Slitrk3 Carboxyl-Terminus Is Critical for GABAergic Synapse Development - Li, Jun; Han, Wenyan; Wu, Kunwei; Li, Yuping Derek; Liu, Qun; Lu, Wei (Frontiers in Molecular Neuroscience, 2019)
Single-passing transmembrane protein, Slitrk3 (Slit and Trk-like family member 3, ST3), is a synaptic cell adhesion molecule highly expressed at inhibitory synapses. Recent studies have shown that ST3, through its extracellular domain, selectively regulates inhibitory synapse development via the trans-synaptic interaction with presynaptic cell adhesion molecule, receptor protein tyrosine phosphatase  (PTP) and the cis-interaction with postsynaptic cell adhesion molecule, Neuroligin 2 (NL2). However, little is known about the physiological function of ST3 intracellular, carboxyl (C)-terminal region. Here we report that in heterologous cells, ST3 C-terminus is not required for ST3 homo-dimerization and trafficking to the cell surface. In contrast, in hippocampal neurons, ST3 C-terminus, more specifically, the conserved tyrosine Y969 (in mice), is critical for GABAergic synapse development. Indeed, overexpression of ST3 Y969A mutant markedly reduced the gephyrin puncta density and GABAergic transmission in hippocampal neurons. In addition, single-cell genetic deletion of ST3 strongly impaired GABAergic transmission. Importantly, wild-type (WT) ST3, but not the ST3 Y969A mutant, could fully rescue GABAergic transmission deficits in neurons lacking endogenous ST3, confirming a critical role of Y969 in the regulation of inhibitory synapses. Taken together, our data identify a single critical residue in ST3 C-terminus that is important for GABAergic synapse development and function.